2021
DOI: 10.1016/j.rssm.2021.100584
|View full text |Cite
|
Sign up to set email alerts
|

Two tales of one city: Unequal vulnerability and resilience to COVID-19 by socioeconomic status in Wuhan, China

Abstract: Although disasters such as pandemics are events that are random in nature, individuals’ vulnerability to natural disasters is inequitable and is shaped by their socioeconomic status (SES). This study examines health inequality by SES amid the COVID-19 pandemic and its underlying mechanisms in Wuhan, China’s epicenter. Using survey data collected in the city during the lockdown period from February 20 to March 6, 2020, we identify two ways in which SES shapes health inequalities—vulnerability and resilience to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
2
29
0
1
Order By: Relevance
“…Regarding low-income parents or ethnic or racial minority groups, it was found that physical distancing measures or quarantines were interwoven with privilege of space or resources. Privilege in terms of higher income and higher socioeconomic status protected individuals from adverse impacts of the pandemic in China ( Wu et al, 2021 ). Higher socioeconomic status, hence higher class, granted access to hygiene supplies, consisted of financial security due to non-precarious employment status, and provided access to a community that offered further resources.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding low-income parents or ethnic or racial minority groups, it was found that physical distancing measures or quarantines were interwoven with privilege of space or resources. Privilege in terms of higher income and higher socioeconomic status protected individuals from adverse impacts of the pandemic in China ( Wu et al, 2021 ). Higher socioeconomic status, hence higher class, granted access to hygiene supplies, consisted of financial security due to non-precarious employment status, and provided access to a community that offered further resources.…”
Section: Resultsmentioning
confidence: 99%
“…Both of these conditions may allow the virus to survive for longer periods of time in rivers and streams, which raises the question of whether SARS-CoV-2 in these waters can be a source of infections and thus contribute to the spread of COVID-19. The implications of this in communities such as Sao Remo would be tremendous as fecal-oral spread of COVID-19 would deapen the socioeconomic inequalities already observed for this disease ( Costa et al, 2020 ; Wu et al, 2021 ). Because of this, we attempted viral culture.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the epidemic has exacerbated the gender inequalities that already existed within families and workplaces [ 32 ]. Wu et al examined the impact of socioeconomic status on health inequalities and found that an individual’s socioeconomic status can influence access to daily protective gear, employment status and community environment, which in turn can affect the risk of infection as well as mental health [ 33 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%